2015
DOI: 10.1002/anie.201509548
|View full text |Cite
|
Sign up to set email alerts
|

Amide‐Substituted Titanocenes in Hydrogen‐Atom Transfer Catalysis

Abstract: Two new catalytic systems for hydrogen-atom transfer (HAT) catalysis involving the N-H bonds of titanocene(III) complexes with pendant amide ligands are reported. In a monometallic system, a bifunctional catalyst for radical generation and reduction through HAT catalysis depending on the coordination of the amide ligand is employed. The pendant amide ligand is used to activate Crabtree's catalyst to yield an efficient bimetallic system for radical generation and HAT catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 47 publications
(40 reference statements)
1
23
0
Order By: Relevance
“…This type of activation would be consistent with recent discoveries regarding the activation of heteroatom–hydrogen bonds by Ti­(III). It has been shown that the O–H hydrogen of water, ,, the O–H hydrogen of methanol, and the N–H hydrogen of amides can all be activated as hydrogen atom donors when they are complexed to Cp 2 TiCl.…”
Section: Resultsmentioning
confidence: 99%
“…This type of activation would be consistent with recent discoveries regarding the activation of heteroatom–hydrogen bonds by Ti­(III). It has been shown that the O–H hydrogen of water, ,, the O–H hydrogen of methanol, and the N–H hydrogen of amides can all be activated as hydrogen atom donors when they are complexed to Cp 2 TiCl.…”
Section: Resultsmentioning
confidence: 99%
“…The diastereoselectivities of the radical reduction (entries 3–5) are typical for radical reactions and rule out different mechanisms of epoxide opening. Gratifyingly, monosubstituted epoxides are opened with a much higher regioselectivity than in Mn‐ or Zn‐based systems …”
Section: Methodsmentioning
confidence: 99%
“…Although the present work describes OH-based proton donors,a ny high-affinity ligand containing as trong X À H bond that is weakened upon coordination to al ow-valent metal should be effective for reduction. Knowles, [18] Gansäuer, [19] and their respective co-workers have demonstrated that activation of an amide NÀHbond by low-valent Ti is an effective method for promoting HAT. To determine if this approach could be employed in the reduction of anthracene, five equivalents of 2-pyrrolidone (based on [SmI 2 ]) was added to asolution of anthracene and SmI 2 .The solution discolored quickly to provide 9,10-dihydroanthracene in quantitative yield.…”
Section: Angewandte Chemiementioning
confidence: 99%